Active management of microgrid network via loss or cost minimization - Goh, Wei Hao. (2011)
A Microgrid is a small-scale low-voltage combined heating and power networks designed to provide electricity and heating load for a small community. It is essentially a low voltage distribution network providing an excellent integration platform for distributed resources, particularly renewable sources, that has become a popular alternative generation in view of the increasing concern on global warming caused by traditional generation method via coal and fuel.